Vulnerability Management Pada Vulnerable Docker Menggunakan Clair Scanner Dan Joomscan Berdasarkan Standar GSA CIO-IT Security-17-80 - Ryan Supriadi Ramadhan; Adityas Widjajarto; Ahmad Almaarif (Jurnal Sistem Komputer dan Informatika (JSON), 2022)
Vulnerabilities in Docker need to be managed considering that this vulnerability is one of the potentials for exploitation, this can happen because Docker is a container related to application and system security. This study analyzes the vulnerability management process in Docker Images and Docker Images Applications using the GSA CIO-IT Security-17-80 standard. This vulnerability search uses two scanning tools, namely Clair Scanner and JoomScan. Vulnerabilities in Docker Images and Docker Images application version - 1, were overcome by creating a new system, namely version - 2 which upgrades the Docker Images software and Docker Images application. The test scenario is run by scanning for vulnerabilities in two versions of the trial system, in the form of a vulnerability report. The data was analyzed using the GSA CIO-IT Security Standard-17-80 which was limited to the stages of Scanning Capabilities, Vulnerability Scanning Process, Vulnerability Scan Reports, Remediation Verification, and Re-Classification of Known Vulnerabilities. The result is the fastest scanning time is in version - 2, the results of the comparison of vulnerabilities obtained are 44.45% on Docker Images and 77.78% on Joomla. So that the contribution that can be given is to provide an overview of the use of the GSA CIO-IT Security-17-80 standard as a guide for managing the security of an IT asset based on the stages carried out. Continuation of research can be in the form of using the 6 stages of GSA with the support of adequate vulnerability data from the right scanner software.